THE RESPONSIBILITY OF THE CENTRAL GOVERNMENT IN ENSURING THE FULFILLMENT OF THE RIGHTS OF FLOOD DISASTER VICTIMS IN ACEH TAMIANG REGENCY FROM THE PERSPECTIVE OF SIYASAH DUSTURIYAH (A REVIEW OF LAW NUMBER 24 OF 2007) - Winda Syaharani; Khalid Khalid (Journal Analytica Islamica, 2026)
Recurring flood disasters in Aceh Tamiang Regency have caused significant social and economic losses to the community and require the state to ensure the fulfillment of disaster victims’ rights. Law Number 24 of 2007 concerning Disaster Management regulates the government’s obligation to provide protection, services, and recovery for affected communities. However, in practice there remains a gap between legal norms and their implementation, particularly regarding the guarantee of the rights of flood victims. This study aims to analyze the responsibility of the central government in ensuring the fulfillment of the rights of flood victims in Aceh Tamiang Regency and to examine it from the perspective of siyasah dusturiyah. The research employs a normative legal method with statutory and conceptual approaches, supported by empirical data related to the conditions of communities affected by floods. The findings reveal that the central government holds constitutional responsibility to guarantee protection and recovery for disaster victims, although its implementation still faces challenges related to institutional coordination and aid distribution. From the perspective of siyasah dusturiyah, such responsibility constitutes a mandate of authority that must be carried out based on the principles of justice, public welfare, and protection of society.